Effect of aggressive chemicals on durability and microstructure properties of concrete containing crushed new concrete aggregate and non-traditional supplementary cementitious materials - Alnahhal, Mohammed Fouad; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Alsubari, Belal; Alqedra, Mamoun A.; Mo, Kim Hung (Elsevier, 2018)
The increasing awareness and usage of traditional supplementary cementitious materials (SCMs) in concrete have pressured the construction industry to look for alternatives to overcome the concerns over their plentiful availability in the future. This research illustrates the performance of recycled aggregate concrete prepared with the incorporation of available industrial by-products, namely rice husk ash (RHA), palm oil fuel ash (POFA) and palm oil clinker powder (POCP) as alternatives for traditional SCMs. The effect of hydrochloric (HCl) acid and magnesium sulfate (MgSO4) attack was evaluated by measuring the change in mass, compressive strength and microstructural analysis. The results revealed that the incorporation of RHA, POFA and POCP up to 30% minimizes concrete deterioration and loss in compressive strength when the specimens were exposed to HCl solution. In addition, the scanning electron microscopy image showed less propagation of micro-cracks caused by expansive ettringite in the case of MgSO4 attack. Further, the X-ray diffraction analysis indicated that RHA is more effective as pozzolanic additive than POFA and POCP. Overall, the RA-based concrete had significant enhancement in its performance against acid and sulfate attacks using alternative SCMs from industrial by-products.